Agglomeration effects on labour demand - Uwe Blien; Kai Kirchhof; Oliver Ludewig (Institut für Arbeitsmarkt- und Berufsforschung (IAB), 2006)
How do agglomeration effects influence the demand for labour? To answer this question, approaches on labour demand are linked with an analysis of the classic 'urbanization effect'. We use models for static and for dynamic labour demand to find out, whether agglomerations develop faster or slower than other regions. Estimations of the static model show the influence of different degrees of regional concentration at the employment level. The model of dynamic labour demand is used to estimate the effect of different regional types on the growth rate of labour demand. The empirical results (received with the linked employer-employee database of the IAB) on long-run or static labour demand indicate substantial agglomeration effects, since c. p. employment is higher in densely populated areas. In the dynamic model, however, labour demand in core cities grows slower than the average. This is not a contradiction. Labour demand is especially high in large cities, but the other areas are slowly reducing the gap.
Keywords: J23; R23; R11; 330; Arbeitskräftenachfrage; Region; regionaler Arbeitsmarkt; regionale Disparität; Ballungsraum; Stadt; Stadtregion; ländlicher Raum; Peripherie; Siedlungsdichte; Beschäftigungseffekte; Dienstleistungsbereich; Suburbanisierung; Nachfrageentwicklung; regionale Faktoren; Beschäftigungsentwicklung; Arbeitsmarktregion; IAB-Linked-Employer-Employee-Datensatz